Successful treatment of polymedicamentous poisoning with metoprolol, diltiazem and cilazapril - Radovanović Milan R.; Miletić Goran M.; Radovanović Mirjana S. (Vojnosanitetski Pregled)
Introduction. Poisoning caused by drugs with cardiodepressive effects is an urgent condition in medicine which is associated with high mortality rate regardless of modern therapeutic methods. Accidental or intentional poisoning whit these drugs produces heart activity depression and cardiovascular collapse as consequences. Current therapy for severe poisoning caused by beta-blockers and calcium channel blockers includes both unspecific and specific antidote therapy whit glucagon, as well as application of adrenergic drugs, calcium, phosphodiesterase inhibitors and hyperinsulinemia/euglycemia therapy. However, even whit the application of these drugs, prompt measures of unspecific detoxication therapy and cardiopulmonary reanimation are crucial for survival of patients with severe poisoning. Case report. A 28-year-old female patient was hospitalized for cardiogenic shock and altered state of conscioussnes (Glasgow coma score = 4), caused by acute poisoning with 2 g of metoprolol (Presolol®), 1.8 g of diltiazem (Cortiazem®) and 50 mg of cilazapril (Zobox®). Prolonged cardiopulmonary resuscitation was applied during the first 16 hours of hospitalization, including administration of crystaline solutions (8 L), 17 mg of adrenaline, 4 mg of atropine, 4 mg of glucagone and 1.6 g of dopamine, with electro-stimulation by temporary pacemaker and mechanical ventilation. In a defined time period, normalized state of consciousness was registered, mechanical ventilation was stopped and normal heart activity and hemodynamic stability were accomplished. During hospitalization the patient was treated for mild pneumonia and after ten days, completely recovered, was released and sent to home treatment. Conclusion. Prompt measures of cardiopulmonary resuscitation and multidisciplinary treatment in intensive care units significantly increase the chances of complete recovery of a patient with severe poisoning caused by drugs with cardiodepressive efects.